Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/slct.202000693
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Microwave‐Assisted Kabachnik‐Fields Reactions

Abstract: A comprehensive evaluation of MW-assisted Kabachnik-Fields reactions (phospha-Mannich condensation) is done to draw the attention of synthetic chemists towards a greener, solvent-free and catalyst-free protocol. The review encompasses the diverse class of α-aminophosphonates and its derivatives synthesized via one-pot three component KF reaction, which finds application in various disciplines of chemistry and covers literature up to 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Such benefits as diversity-oriented synthesis, combinatorial library generation, and convergence/divergence acknowledge many aspects of GC and the sustainable synthesis process. For the purpose of green synthesis, well-known classical MCRs are Biginelli, Strecker, Mannich, Passerini, Ugi, Orru, Hantzsch, Petasis, Groebke–Blackburn–Bienayme, , Kabachnik–Fields, Willgerodt–Kindler, Bucherer–Bergs, Gewald reactions, etc. The mentioned MCRs are used directly to synthesize many pharmaceuticals and key intermediates following the major principles of GC.…”
Section: Multicomponent Reactions For Green and Sustainable Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Such benefits as diversity-oriented synthesis, combinatorial library generation, and convergence/divergence acknowledge many aspects of GC and the sustainable synthesis process. For the purpose of green synthesis, well-known classical MCRs are Biginelli, Strecker, Mannich, Passerini, Ugi, Orru, Hantzsch, Petasis, Groebke–Blackburn–Bienayme, , Kabachnik–Fields, Willgerodt–Kindler, Bucherer–Bergs, Gewald reactions, etc. The mentioned MCRs are used directly to synthesize many pharmaceuticals and key intermediates following the major principles of GC.…”
Section: Multicomponent Reactions For Green and Sustainable Synthesismentioning
confidence: 99%
“…The Kabachnik−Fields reaction is a 3-CR among an amine, a carbonyl, and a hydrophosphoryl compound to obtain αaminophosphonates, which is an important scaffold to generate peptidomimetic compounds (Scheme 116). 263 The pathway of the Kabachnik−Fields reaction strictly varies on the nature of the substrates. The amine and hydrophosphoryl compounds form a complex first, and then, the carbonyl compound reacts with the intermediate.…”
Section: The Kabachnik−fields Reactionmentioning
confidence: 99%
“…[42] in this respect, the use of microwave/ultrasound irradiations as an alternative to conventional heating is an-other way to maintain a safer and greener synthesis. [43] On the other hand, the sulfa drugs have received great deal of attention as these compounds have been found to exhibit several biological activities, such as antibacterial, [44] anticonvulsant, [45] and anti-hypoglycemic, [46] have also been recognized as inhibitors of HIV-1 proteinase, [47] glycogen phosphorylase, [48] and the carbonic anhydrase metalloenzyme (CA, EC 4.2.1.1). [49,50] The introduction of these moieties as precursors in the synthesis of novel α-aminophosphonates compounds can further modulate the proprieties of a biomolecules, due to modification in chemical reactivity, lipophilicity, solubility, metabolic stability, conformation and hydrogen-bond ability.…”
Section: Introductionmentioning
confidence: 99%
“…But that; is also associated with high costs, non‐reusability, and toxic wastes, [41] that‘s why designing catalyst‐free synthetic protocols that are at the same time efficient and greener has been highly requested [42] . in this respect, the use of microwave/ultrasound irradiations as an alternative to conventional heating is an‐other way to maintain a safer and greener synthesis [43] …”
Section: Introductionmentioning
confidence: 99%
“…2 Numerous synthetic approaches have been developed to construct the key P–C–N bonds of α-amino phosphonates and their derivatives. 3 For example, Pudovik condensation, 4 Kabachnik–Fields reaction, 5 and the newly developed condensation reactions between H-phosphonates and aldehydes or imines under Lewis acid-catalyzed, 6 catalyst-free, 7 microwave-promoted 8 and asymmetric conditions 9 are commonly used to access α-aminophosphonates. 10 Carboxamides are readily available and bench-stable chemical feedstock, and recent studies have demonstrated that carboxamides can be used as precursors of imines, enamines or hemiaminals.…”
Section: Introductionmentioning
confidence: 99%